Innovative catalytic systems driving sustainable olefin polymerization: Recent advances and green chemistry approaches - Farabi Hossain; Md Enamul Hoque (Polyolefins Journal)
This mini-review addresses the burgeoning requirements for environmentally friendly processes in the polymer industry, focusing on recent progress in developing catalytic systems for sustainable olefin polymerization. Improvements in homogeneous and heterogeneous catalyst design have resulted in greater control over polymer properties (molecular weight, tacticity, comonomer incorporation). Particularly, Group 4 metallocene and post-metallocene catalysts have enjoyed high activity and a degree of control over polymer microstructure. Late transition metal catalysts (nickel and palladium complexes in particular) afford unique advantages in producing branched polyethylene and conducting polymerizations in polar solvents. Computational studies and novel support strategies have yielded improvements for heterogeneous Ziegler-Natta catalysts. Potential for reducing environmental impact through green catalysis approaches include enzyme-based systems, ionic liquids, and photoactivated catalysts. These catalytic advances have permitted previously unavailable control over polymer properties, including molecular weight distribution and functional group incorporation. Challenges remain regarding the stability of the catalysts, incorporation of comonomer, and economic feasibility. Future work focuses on new ligand design, extending the monomer scope to include renewable feeds tocks and improving the activation procedures. There is a critical need to integrate computational modeling, machine learning, and advanced characterization techniques to facilitate catalyst discovery and understanding of complex structure-property relationships. In general, this review demonstrates the ongoing development of olefin polymerization toward more sustainable practices and describes the important role of advanced catalytic systems in determining the future of the polymer industry).